English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

How would I solve that? I tried making it : ln y = sin(x)ln x but I'm not sure where to go from there.

2007-01-09 15:54:11 · 1 answers · asked by Anonymous in Science & Mathematics Mathematics

1 answers

Well that's quite good, now you have:

[x→0+]lim sin x ln x, which gives you the indeterminate form 0*-∞. So rewrite this as:

[x→0+]lim ln x/(1/sin x)

Which now gives you the indeterminate -∞/∞, so you can employ L'hopital's rule:

[x→0+]lim (1/x)/(-csc x cot x)

Algebraic manipulation yields:

[x→0+]lim (-sin x)/x tan x

Which beomes the determinate form:

-1*0 (since [x→0+]lim (-sin x)/x = -1 and [x→0+]lim tan x = 0)

Which is simply 0. So ln y=0, y=1. And we are done.

Edit: corrected a sign error.

Edit: corrected another sign error which I missed when correcting the first sign error. Also changed 0 to 0+ to improve accuracy.

2007-01-09 16:11:50 · answer #1 · answered by Pascal 7 · 0 0

fedest.com, questions and answers